2004
DOI: 10.1074/jbc.m401389200
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the Circadian Oscillator in Xenopus Retinal Photoreceptors by Protein Kinases Sensitive to the Stress-activated Protein Kinase Inhibitor, SB 203580

Abstract: Circadian rhythms are generated by transcriptional and translational feedback loops. Stress-activated protein kinases (SAPKs) are known to regulate transcription factors in response to a variety of extracellular stimuli. In the present study, we examined whether the SAPKs play a role in the circadian system in cultured Xenopus retinal photoreceptor layers. A 6-h pulse of SB 203580, an inhibitor of SAPKs, reset the circadian rhythm of melatonin in a phase-dependent manner similar to dark pulses. This phase-shif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
20
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 50 publications
0
20
0
Order By: Relevance
“…Following inhibition of p38 MAPK activation, using its inhibitor SB203580, Hayashi et al (2003) found the free-running period of the rhythm of melatonin release in cultured chick pineal cells extended from 24.0±0.3 h to 28.7±1.1 h. They also reported that a 4 h-pulse of SB203580 given during the subjective day could delay the phase of the melatonin release rhythm. SP600125 could also dose-dependently delay the phase of the rhythm of melatonin release from Xenopus photoreceptor layers (Hasegawa and Cahill, 2004). The similar effects of SB203580 and SP600125 might suggest that p38 MAPK and JNK are both involved in the regulation of the circadian molecular clockwork.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Following inhibition of p38 MAPK activation, using its inhibitor SB203580, Hayashi et al (2003) found the free-running period of the rhythm of melatonin release in cultured chick pineal cells extended from 24.0±0.3 h to 28.7±1.1 h. They also reported that a 4 h-pulse of SB203580 given during the subjective day could delay the phase of the melatonin release rhythm. SP600125 could also dose-dependently delay the phase of the rhythm of melatonin release from Xenopus photoreceptor layers (Hasegawa and Cahill, 2004). The similar effects of SB203580 and SP600125 might suggest that p38 MAPK and JNK are both involved in the regulation of the circadian molecular clockwork.…”
Section: Discussionmentioning
confidence: 74%
“…The related p38 MAPK and ERK subfamilies activation were found rhythmic in tissues containing circadian oscillators. First, p38 MAPK phosphorylation levels oscillate in the rat and chick pineal gland where these kinases have been shown to control the period and phase of circadian rhythms (Hayashi et al, 2003;Hasegawa and Cahill, 2004). Second, daily and circadian rhythms of ERK activations occur respectively in the rat pineal gland (Ho et al, 2003), and in both Syrian hamster and mouse SCN (Obrietan et al, 1998;Pizzio et al, 2003).…”
mentioning
confidence: 99%
“…The ϳ25 mV hyperpolarizing shift in V 1/2 caused by inhibition of p38 MAPK activity suggests that constitutive (i.e., tonically active) intracellular p38 MAPK activity is a major determinant of normal h-channel properties. A similar phenomenon has been shown for tyrosine kinases in the maintenance of resting CNG (cyclic nucleotidegated) channel properties (Kramer and Molokanova, 2001), and there is evidence in cell types as diverse as Xenopus oocytes, human embryonic kidney cells, and rat hepatocytes that constitutive p38 MAPK activity regulates a variety of signaling pathways (Feranchak et al, 2001;Hasegawa and Cahill, 2004;Samuvel et al, 2005). The present results, however, do not show whether p38 MAPK phosphorylates specific residues on the HCN protein, leaving open the possibility that downstream effectors of p38 MAPK mediate its actions on I h .…”
Section: Discussionmentioning
confidence: 95%
“…In a Xenopus photoreceptor model of circadian rhythmicity, administration of SB203580, a nonselective inhibitor of CKI, reset the circadian pattern of melatonin secretion as a function of phase (Hasegawa and Cahill, 2004). CKI-7, a more selective CKI inhibitor, reduced PER degradation, delayed the nuclear entry of the protein, and lengthened the duration of nuclear residence (Miyazaki et al, 2004).…”
mentioning
confidence: 99%